The Determinants That Make Seniors Move to Commercial Care Homes - Boruta, Marcin (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The processes of aging bring about a need for scientific activity focused on senior housing. Researchers are increasingly more interested in housing offers which should be customized to seniors’ needs and provide a wide choice of solutions responding to a highly heterogeneous nature of senior population. Of the forms of residence available to seniors in Poland, commercial home cares are worth noting in particular. The purpose of this article is to identify the profile of an average resident of a commercial home care, as well as to understand the reasons why seniors migrate to such a form of living. The author presents herein the results of pilot surveys conducted across commercial care homes in the region of Wielkopolska. The survey results indicate that a majority of migration is caused by health reasons and the fact that housing conditions are not suitable for the needs of seniors. The residents of commercial care homes are mainly retired lonely women who have children and fall into the most elderly group of seniors who are 75 years old or older.